Working Conditions and Problems of Domestic Child Labour in Kathmandu Metropolitan City - Duwadi, Pampha (Voice of Teacher, 2021)
In general, the children working in employer’s house for household work with or without wage are known as domestic child worker. Domestic child workers are seen to operate household chores such as cooking, washing, cleaning and taking care of employer families' children. The study was conducted in Kathmandu Metropolitan city, ward no. 16 of Bagmati province in 2020. This paper aimed to highlight the social issues, primarily the working conditions of child labour in the study area. The purpose of the study was to identify the major problems faced by domestic child workers from development perspective. The study was based primarily on both quantitative and qualitative research methods. The study revealed that employer families have appeared to involve domestic child Labour in household chores without either pay that is insufficient or without any pay as compensation. The study also found that in the name of providing them with education and promise of better life, these child labours had been misused and exploited. The long working hours and unpaid labour and merely any facilities of education and health services, child labours have been both physically and mentally abused in majority of the cases. The study also found that guardians and relatives were agents to fix the domestic child worker. The money earned by them was kept by their parents. Domestic child workers had been low paid and therefore exploited in terms of remuneration, lack basic amenities and even lack security.